Finished bacterial genomes from shotgun sequence data - Ribeiro, Filipe J.; Przybylski, Dariusz; Yin, Shuangye; Sharpe, Ted; Gnerre, Sante; Abouelleil, Amr; Berlin, Aaron M.; Montmayeur, Anna; Shea, Terrance P.; Walker, Bruce J.; Young, Sarah K.; Russ, Carsten; et al. (Genome Research, 2012)
Exceptionally accurate genome reference sequences have proven to be of great value to microbial researchers. Thus, to date, about 1800 bacterial genome assemblies have been “finished” at great expense with the aid of manual laboratory and computational processes that typically iterate over a period of months or even years. By applying a new laboratory design and new assembly algorithm to 16 samples, we demonstrate that assemblies exceeding finished quality can be obtained from whole-genome shotgun data and automated computation. Cost and time requirements are thus dramatically reduced.
10.1101/gr.141515.112